The Challenges to the Teaching Staff in Practicing their Social Responsibility Role at Saudi Universities - Alatawi, Ahlam Qasim Salman; Alzahrani, Amal Mohamad Abdallah (The Arab Journal of Administration, 2024)
This study aims to identify the organizational challenges to teaching staff in practicing social responsibility in Saudi universities with and identification to the human challenges to the practice of social responsibility by teaching staff in universities, and to identify the cultural challenges to the practice of social responsibility by teaching staff in universities. Moreover, to submit proposals for the contribution of teaching staff to activating social responsibility in universities. The descriptive approach used in a social survey method, and the research community consisted of teaching staff in Saudi universities, namely: (King Khalid University, Tabuk University, King Abdulaziz University), where a random sample of (105) members of the staff obtained. A questionnaire used for data collection and well prepared to address the most important challenges of practicing social responsibility by teaching staff, including organizational, human, and cultural challenges. The study resulted that the most important organizational challenges to practicing social responsibility by teaching staff in universities are: the lack of organizing seminars to outline the requirements of social responsibility programs necessary for society, while the key challenges from human perspective to practice social responsibility by teaching staff in universities are: the teaching staff encounter many issues among them is the lack of time available for social responsibility programs, and the most important cultural challenges to the practice social responsibility by teaching staff in universities are: The lack of external community adoption of research results prepared by teaching staff. The most important recommendation for the contribution of teaching staff to activating social responsibility in universities is the involvement of teaching staff in internal and external community activities and events. The two female researchers have highlighted the necessity for the competent departments at the Ministry of Education to hold local and international conferences and organize seminars to study the requirements of social responsibility programs at universities and vesting the university leaders and deanships with necessary administrative and organizational powers to activate social responsibility in universities.